EFEKTIVITAS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN PENALARAN GEOMETRIS SISWA KELAS VIII - Rusi Ulfa Hasanah (State Islamic University of North Sumatra, 2019)
The aim of this research was to see the effectiveness of interactive multimedia in terms of geometric reasoning skill of junior high school students in grade VIII. The interactive multimedia used was Flash with the content is polyhedron for grade VIII students. The subjects were students of class VIII.7 SMPN 5 Yogyakarta. The instruments used were the geometric reasoning skill tests. Interactive multimedia is effective if at least 75% of students reach the minimum criteria of mastery learning in geometric reasoning skill test and at least 75% of students' proportion is categorized in high category or above. The result of students' geometric reasoning skill test shows that the developed product is in effective category. This is because 75% of students reach the minimum criteria of mastery learning. Based on the hypothesis test with 5% of significance level, it is obtained the proportion of students who had geometric reasoning skill in high category or above is more than or equal to 75%.